Respuesta :
given (x - 1)(x + 1)(x + 5 ) =0
that is a product of factors equating to zero
to solve equate each factor to zero and solve for x
x - 1 = 0 ⇒ x = 1
x + 1 = 0 ⇒ x = - 1
x + 5 = 0 ⇒ x = - 5
Factorization involves splitting a function into factors.
The values of x are: -5, -1 and 1
The function is given as:
[tex]\mathbf{P(x) = (x - 1)(x + 1)(x + 5)}[/tex]
Set to 0
[tex]\mathbf{ (x - 1)(x + 1)(x + 5) = 0}[/tex]
Split
[tex]\mathbf{ (x - 1) = 0\ or\ (x + 1) = 0\ or\ (x + 5) = 0}[/tex]
Remove brackets
[tex]\mathbf{ x - 1 = 0\ or\ x + 1 = 0\ or\ x + 5 = 0}[/tex]
Solve for x
[tex]\mathbf{ x = 1\ or\ x= -1\ or\ x =- 5}[/tex]
Hence, the values of x are: -5, -1 and 1
Read more about factorization at:
https://brainly.com/question/11579290